Retrograde Access to Seal a Large Coronary Vessel Balloon Perforation Without Covered Stent Implantation - Kartas, Anastasios (JACC Case Rep, 2021)
The sealing of a large vessel coronary perforation during percutaneous coronary intervention typically requires the deployment of 1 or more covered stents. A novel approach to seal a life-threatening perforation caused by unnoticed wire-exit and balloon dilation, utilizing retrograde techniques, without a covered-stent is described. (Level of Difficulty: Advanced.)